The effect of a preconception care outreach strategy: the Healthy Pregnancy 4 All study - Meertien K. Sijpkens; Sabine F. van Voorst; Lieke C. de Jong-Potjer; Semiha Denktaş; Arnoud P. Verhoeff; Loes C. M. Bertens; Ageeth N. Rosman; Eric A. P. Steegers (BMC, 2019)
Abstract Background Preconception care has been acknowledged as an intervention to reduce perinatal mortality and morbidity. However, utilization of preconception care is low because of low awareness of availability and benefits of the service. An outreach strategy was employed to promote uptake of preconception care consultations. Its effect on the uptake of preconception care consultations was evaluated within the Healthy Pregnancy 4 All study. Methods We conducted a community-based intervention study. The outreach strategy for preconception care consultations included four approaches: (1) letters from municipal health services; (2) letters from general practitioners; (3) information leaflets by preventive child healthcare services and (4) encouragement by peer health educators. The target population was set as women aged 18 to 41 years in 14 Dutch municipalities with relatively high perinatal morbidity and mortality rates. We evaluated the effect of the outreach strategy by analyzing uptake of preconception care consultations between February 2013 and December 2014. Registration data of applications for preconception care as well as participant questionnaires were obtained for analysis. Results The outreach strategy led to 587 applications for preconception care consultations. The majority of applications (n = 424; 72%) were prompted by the invitation letters (132,129) from the municipalities and general practitioners. The effect of the municipal letter seemed to fade out after 3 months. Conclusions Outreach strategies amongst the general population promote uptake of preconception care consultations, although on a small scale and with a temporary effect.